Environmental ethics and uncertainty wrestling with wicked problems - Bauman, Whitney; O'Brien, Kevin J. (Kevin James) 1977- (London Routledge, 2020)
"This book offers a multidisciplinary (theology, philosophy, and sociology) environmental approach to ethics in response to the contemporary challenge of climate change caused by globalized economics and consumption. This book synthesises the incredible complexity of the problem and the necessity of action in response, highlighting the unambiguous problem facing humanity in the 21st century, but arguing that it is essential to develop an ethics housed in ambiguity in response. Environmental Ethics and Uncertainty is divided into theoretical and applied chapters, with the theoretical sections engaging in dialogue with theorists and scholars from a variety of disciplines, while the applied chapters offer insight from 20th century activists who demonstrate and/or illuminate the theory, including Martin Luther King, Rachel Carson and Frank Lloyd Wright. This book is written for scholars and students in the interdisciplinary field of environmental studies and the environmental humanities, and will appeal to courses in religion, philosophy, ethics, politics and social theory"--
Introduction : the problem with knowing the answer -- Ethical action in an ambiguous world -- The depths of ambiguity : ethical pluralism and wonder in Marjory Stoneman Douglas and Rachel Carson -- Good and evil without progress -- Complexity In action : the challenging uncertainties of Martin Luther King, Jr. and Malcolm X -- Loving the world without certainty -- Built-in ambiguity : the spirituality and utopianism of Frank Lloyd Wright -- Concluding ideas on ambiguous time -- Concluding practices for an uncertain stand : fracking, protesting, and engineering the climate.
Includes bibliographical references and index.
Keywords: Environmental ethics; Uncertainty; Global environmental change -- Moral and ethical aspects; Globalization -- Economic aspects; Globalization -- Environmental aspects